Causal Factors of Stress Experienced by Caregivers of Schizophrenia Patients - Vetalu Nyekha; Prachi Ghildyal (International Journal of Indian Psychȯlogy, 2025)
Caregiver stress is a widely known phenomenon that is experienced by people who are in the role of giving care to someone. Although the cause differs from one to another, the stress is known to be high among caregivers who take care of people with schizophrenia. Schizophrenia is a chronic mental disorder that does not only affect the patient significantly but also the person who is a primary caregiver of the patient. Caregiver stress here refers to the psychological as well as strain that is experienced by the individuals who provide care to a person diagnosed with schizophrenia. This article looks at literatures along with data from an ongoing research to explore the factors that contribute to the caregiver stress.